2015
DOI: 10.1177/0898264315611665
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Outdoor Mobility in Vulnerable Community-Dwelling Elderly

Abstract: Declining health status and functional limitations are risk factors that pose a threat to outdoor mobility in the frail elderly, while housing barriers and community accessibility also merit attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
(39 reference statements)
1
28
0
Order By: Relevance
“…Walking is recommended [ 67 , 98 100 ]. The number of repetition of the basic locotra is increased, and other exercises, such as heel raise and front lunges, are added.…”
Section: Locomotion Trainingmentioning
confidence: 99%
“…Walking is recommended [ 67 , 98 100 ]. The number of repetition of the basic locotra is increased, and other exercises, such as heel raise and front lunges, are added.…”
Section: Locomotion Trainingmentioning
confidence: 99%
“…Fear of falling is a concern about falling over which results in activity avoidance [21] and is common among older adults, whether they have experienced a fall or not [21,22]. Concerns about falling over can lead to reductions in daily mobility and associated physical activity, an increased risk of falls and threaten the wellbeing of older adults [19,[23][24][25][26][27][28]. Fear of falling is associated with reduced social activity, depression, decreased quality of life, difficulties with activities of daily living and functional disability [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the associations of PREDICTORS OF OUT-OF-HOME TIME AMONG OLDER ADULTS 4 these social environmental factors with out-of-home behavior are still inconclusive (Fujita et al, 2004;Ganguli et al, 1996;Jing et al, 2017;Murayama et al, 2012;Nakamura & Yamada, 2009;Negron-Blanco et al, 2016;Todo et al, 2015). On the other side, regarding the physical environmental factors, while Japanese studies (Hirai et al, 2015;Murayama et al, 2012) have reported the associations of poor food accessibility and daily errands with homebound status among older adults, a previous study in the United States did not support these results (Smith et al, 2016). Inconsistent findings for environmental correlates of out-of-home behavior in previous studies would be derived from methodological limitations among them.…”
Section: Introductionmentioning
confidence: 81%
“…Although various studies have identified determinants of homebound status and out-of-home behavior (Fujita et al, 2004;Ganguli, Fox, Gilby, & Belle, 1996;Jing, Wang, Zhang, Yao, & Xing, 2017;Murayama, Yoshie, Sugawara, Wakui, & Arami, 2012;Nakamura & Yamada, 2009;Negrón-Blanco et al, 2016;Smith, Chen, Clarke, & Gallagher, 2016;Todo et al, 2015), evidences about the environmental determinants of out-of-home behavior among older adults are still inconsistent. According to physical activity studies using an ecological model, out-of-home time among older adults would be influenced by both social and physical environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation